2021
DOI: 10.1186/s12978-021-01264-y
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptation of patients diagnosed with human papillomavirus: a grounded theory study

Abstract: Background Human papillomavirus is the most common cause of sexually transmitted diseases. Various studies report that positive human papillomavirus diagnosis results in psychosexual issues for the infected and reduces their quality of life. However, the adaptation of the infected has not been addressed yet. The present study aims to identify the process by which individuals infected with human papillomavirus adapt to their disease. Method This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The inclusion criteria were having been diagnosed with HPV con rmed by gynecologic oncologists (33), less than 6 months having passed since the test (27), not having neurological disorders (34), being sexually active (17), and willingness to participate in the study and ll the informed consent form (33).…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“…The inclusion criteria were having been diagnosed with HPV con rmed by gynecologic oncologists (33), less than 6 months having passed since the test (27), not having neurological disorders (34), being sexually active (17), and willingness to participate in the study and ll the informed consent form (33).…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in the pdf-version of the article the statement in the Funding-section was incorrect. It should have read “Shiraz University of Medical Sciences provided funding for the research.…”
Section: Correction To: Reprod Health (2021) 18:213 101186/s12978-021-01264-ymentioning
confidence: 99%